778Risk of 27 cancer types in relation to tobacco smoking: cohort study involving 229, 028 Australians. (2nd September 2021) - Weber, Marianne; Sarich, Peter; Vaneckova, Pavla; Wade, Stephen; Banks, Emily; Egger, Sam; Ngo, Preston; Joshy, Grace; Goldsbury, David; Yap, Sarsha; Vassallo, Amy; Feletto, Eleonora; et al.
Abstract: Background: Tobacco smoke is a known carcinogen and the magnitude of smoking-related cancer risk varies according to time and population. Local, contemporary evidence can drive appropriate tobacco control. We provide comprehensive cancer risk estimates related to smoking in the population-based, New South Wales (NSW) 45 and Up Study. Methods: We estimated smoking-related hazard ratios (HR) for cancer using Cox proportional hazards regression using linked questionnaire (2006-2009) and incident cancer data (n ≥ 50 cases per cancer type), from the NSW Cancer Registry (to December 2013) (via CHeReL). Results: Of 18, 475 cancers among 229, 028 participants aged ≥45 years, current smokers had significantly increased risks of cancers of the lung, larynx, head and neck, oesophagus, liver, bladder, pancreas, stomach, colorectum, and cancers with unknown primary site, compared to never-smokers; lung cancer risk was markedly elevated, including for current-smokers of 1-5 cigarettes/day (HR = 9.25, 95%CI=5.2-16.6), increasing to 38.39 (26.2-56.2) for current-smokers of > 30 cigarettes/day. Quitting substantively decreased cancer risk compared to continued smoking, with lung cancer risk decreasing with decreasing age at quitting ( p( trend)<0.05), however risks remained elevated for those quitting aged >25 compared to never-smokers (1.73, 1.1-2.6 for age 26-30 years). An estimated 20% of current-smokers in Australia will get lung cancer during their lifetime versus 1.6% of never-smokers. Conclusions: Smoking-attributable cancer risks in Australia are significant, comparable to contemporary risks from other developed nations. Key messages: Smokers – including "light" smokers – are at high cancer risk, with ∼one-fifth of Australian lifetime smokers developing lung cancer. Quitting is beneficial. Continued investment in tobacco control is essential.